Flame retardant high-strength composite plastic and preparation method thereof
By modifying and compositeing the magnesium oxide in PET materials, the introduction of Schiff alkali structure and highly stable benzene ring structure is solved, and the performance degradation of PET materials in high temperature environments is significantly improved, which has significantly improved its mechanical strength and flame retardant properties. .
Patent Information
- Application Number
- CN202411687832.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
PET materials are prone to thermal degradation in high temperature environments, resulting in reduced performance and need to have high strength and flame retardant properties in food packaging, but the prior art is difficult to effectively improve its mechanical strength and flame retardant properties.
By modifying hydroxycinnamic acid and compounding with magnesium oxide, grafting of cysteine is promoted, and the chemical bonding between amino and aldehyde groups is introduced, the Schiff base structure and a large number of hydroxy and carboxylic functional groups are introduced, and the structure of plastic materials is improved. Density. At the same time, by modifying magnesium oxide in organic matter, a highly stable benzene ring structure is introduced to improve compatibility, and a compatibility agent is added to enhance the dispersion and interface binding force of the modified magnesium oxide with glass fibers.
It significantly enhances the mechanical strength and flame retardant properties of plastics, improves the compatibility and dispersion of magnesium oxide in PET systems, and ensures the performance stability of plastics in high temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastics and relates to a flame retardant high-strength composite plastic and a preparation method thereof. Background Art
[0002] PET material, namely polyethylene terephthalate, has been widely used in the field of food plastic products due to its excellent physical and chemical properties. PET material has good transparency, heat resistance and chemical resistance, making it an ideal choice for food packaging. In addition, PET material is also lightweight, environmentally friendly and recyclable, which further enhances its application value in food plastic products. First of all, PET material is widely used in food packaging. Due to its excellent transparency, PET material is often used to make packaging materials such as beverage bottles, food cans and plastic wrap. These packaging materials can not only effectively protect food and extend its shelf life, but also allow consumers to clearly see the food in the package, enhancing the shopping experience. In addition, the heat resistance of PET material makes it suitable for microwave heating and high-temperature sterilization, meeting the needs of modern consumers for convenience and safety.
[0003] When it comes to PET plastics needing to have high strength, it means that the material should have excellent mechanical strength and be able to withstand strong pressure and impact to ensure that the food packaging is intact and durable. In order to meet these performance standards, PET materials must be added with specific additives or undergo special modification during the production process to enhance its flame retardancy and improve its strength.
[0004] Although PET (polyethylene terephthalate) is prone to thermal degradation under high temperature conditions, resulting in reduced performance, the introduction of inorganic flame retardant magnesium oxide significantly improves its mechanical strength and flame retardant properties. Magnesium oxide is a flame retardant widely used in a variety of materials, especially in plastic products. It can decompose rapidly at high temperatures, releasing a large amount of water vapor, effectively inhibiting the spread of flames. In addition, magnesium oxide also has excellent thermal and chemical stability, and can maintain stable performance under high temperature and high humidity conditions. However, the dispersibility of magnesium oxide in PET plastic is the key factor that determines its performance improvement effect. Summary of the invention
[0005] The object of the present invention is to provide a flame-retardant high-strength composite plastic and a preparation method thereof. The present invention adopts p-hydroxycinnamic acid for modification, and then the modified cinnamic acid is compounded with magnesium oxide to promote the grafting of cysteine, and then the modified magnesium oxide is connected by chemical bonds between amino groups and aldehyde groups, so that the modified magnesium oxide contains a Schiff base structure and a large number of hydroxyl and carboxyl functional groups, thereby improving the compactness of the plastic material structure, thereby significantly enhancing the mechanical strength and flame retardant properties of the plastic; in addition, the magnesium oxide is modified by organic matter and a large number of highly stable benzene ring structures are introduced, thereby improving the compatibility of magnesium oxide in a polyethylene terephthalate system, and combined with the addition of a compatibilizer, the dispersibility and interface bonding force of the modified magnesium oxide and glass fiber in the system are further enhanced, thereby further improving the mechanical strength and flame retardant properties of the plastic.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A flame-retardant high-strength composite plastic comprises the following components by weight: 100-110 parts of polyethylene terephthalate, 15-20 parts of modified magnesium oxide, 3-4 parts of glass fiber and 6-8 parts of a compatibilizer; the compatibilizer is a styrene-glycidyl methacrylate copolymer.
[0008] Wherein, the preparation method of the modified magnesium oxide comprises the following steps:
[0009] 1) After magnesium oxide and anhydrous ethanol are stirred and mixed, modified cinnamic acid is added for ultrasonic treatment, cysteine and a photoinitiator are added and mixed, and then ultraviolet irradiation is performed, and solids are filtered, washed, and vacuum dried to constant weight to obtain prefabricated magnesium oxide;
[0010] 2) After the prefabricated magnesium oxide and anhydrous ethanol are mixed and preheated, protocatechuic aldehyde is added and stirred at a constant temperature, the mixture is allowed to stand, the solid is filtered out, washed, and vacuum dried to a constant weight to obtain modified magnesium oxide.
[0011] As a preferred technical solution of the present invention, in step 1), the stirring and mixing is stirring at a speed of 300-400r / min for 20-30min; the ultrasonic treatment is ultrasonic treatment at a power of 300-400W for 15-20min; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365nm for 6-8h; the washing is washing three times with anhydrous ethanol; and the temperature of the vacuum drying is 70-80°C.
[0012] As a preferred technical solution of the present invention, in step 1), the mass ratio of the magnesium oxide, anhydrous ethanol, modified cinnamic acid, cysteine and photoinitiator is 16:45-50:4-4.5:2.0-2.3:0.10-0.12; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0013] As a preferred technical solution of the present invention, in step 2), the constant temperature stirring is stirring at 60-65°C for 6-8 hours; the standing time is 2-3 hours; and the washing is washing with anhydrous ethanol three times.
[0014] As a preferred technical solution of the present invention, in step 2), the mass ratio of the prefabricated magnesium oxide, anhydrous ethanol and protocatechuic aldehyde is 19-20:60-70:3.4-4.0.
[0015] As a preferred technical solution of the present invention, the preparation method of the modified cinnamic acid comprises the following steps: mixing p-hydroxycinnamic acid and sodium hydroxide aqueous solution, adjusting the pH value, adding chloroacetic acid, heating and stirring, filtering out solids, washing, and vacuum drying to constant weight to obtain modified cinnamic acid;
[0016] As a preferred technical solution of the present invention, in the preparation of the modified cinnamic acid, the pH value is adjusted to 10-13; the heating and stirring is stirring at 90°C for 7-8h; the washing is washing twice with acetone and deionized water respectively; the vacuum drying temperature is 80°C; the mass ratio of p-hydroxycinnamic acid, sodium hydroxide aqueous solution and chloroacetic acid is 0.8-1.0:10-12:0.9-1.2; the sodium hydroxide aqueous solution is prepared by mixing sodium hydroxide and deionized water in a mass ratio of 1:13.
[0017] A method for preparing a flame-retardant high-strength composite plastic comprises the following steps: polyethylene terephthalate, modified magnesium oxide, glass fiber and a compatibilizer are mixed according to weight proportions, melt-extruded at a temperature of 190-210 DEG C, and granulated to obtain the composite plastic.
[0018] Beneficial effects of the present invention:
[0019] The invention adopts p-hydroxycinnamic acid for modification, and then compounds the modified cinnamic acid with magnesium oxide, promotes the grafting of cysteine, and then connects the modified magnesium oxide with the aldehyde group through the chemical bond of the amino group, so that the modified magnesium oxide contains a Schiff base structure and a large number of hydroxyl and carboxyl functional groups, improves the compactness of the plastic material structure, and thus significantly enhances the mechanical strength and flame retardant properties of the plastic; in addition, the magnesium oxide is modified with organic matter and a large number of highly stable benzene ring structures are introduced, so that the compatibility of magnesium oxide in a polyethylene terephthalate system is improved, and combined with the addition of a compatibilizer, the dispersibility and interface bonding force of the modified magnesium oxide and glass fiber in the system are further enhanced, and the mechanical strength and flame retardant properties of the plastic are further improved. DETAILED DESCRIPTION
[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0021] Example 1
[0022] A flame-retardant high-strength composite plastic comprises the following components by weight: 100 parts of polyethylene terephthalate, 15 parts of modified magnesium oxide, 3 parts of glass fiber and 6 parts of a compatibilizer; the compatibilizer is a styrene-glycidyl methacrylate copolymer.
[0023] Wherein, the preparation method of the modified magnesium oxide comprises the following steps:
[0024] 1) After magnesium oxide and anhydrous ethanol are stirred and mixed, modified cinnamic acid is added for ultrasonic treatment, cysteine and a photoinitiator are added and mixed, and then ultraviolet irradiation is performed, and solids are filtered, washed, and vacuum dried to constant weight to obtain prefabricated magnesium oxide;
[0025] 2) After the prefabricated magnesium oxide and anhydrous ethanol are mixed and preheated, protocatechuic aldehyde is added and stirred at a constant temperature, the mixture is allowed to stand, the solid is filtered out, washed, and vacuum dried to a constant weight to obtain modified magnesium oxide.
[0026] In step 1), the stirring and mixing is stirring at a speed of 300 r / min for 20 minutes; the ultrasonic treatment is ultrasonication at a power of 300 W for 15 minutes; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 6 hours; the washing is washing three times with anhydrous ethanol; the temperature of the vacuum drying is 70°C; the mass ratio of the magnesium oxide, anhydrous ethanol, modified cinnamic acid, cysteine and photoinitiator is 16:45:4:2.0:0.10; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0027] In step 2), the constant temperature stirring is stirring at 60° C. for 6 hours; the standing time is 2 hours; the washing is washing with anhydrous ethanol three times; the mass ratio of the prefabricated magnesium oxide, anhydrous ethanol and protocatechuic aldehyde is 19:60:3.4.
[0028] The preparation method of the modified cinnamic acid comprises the following steps: mixing p-hydroxycinnamic acid and a sodium hydroxide aqueous solution, adjusting the pH value, adding chloroacetic acid, heating and stirring, filtering out solids, washing, and vacuum drying to constant weight to obtain modified cinnamic acid;
[0029] In the preparation of the modified cinnamic acid, the pH value is adjusted to 10; the heating and stirring is stirred at a temperature of 90°C for 7 hours; the washing is washed twice with acetone and deionized water alternately; the temperature of the vacuum drying is 80°C; the mass ratio of the p-hydroxycinnamic acid, the sodium hydroxide aqueous solution and the chloroacetic acid is 0.8:10:0.9; the sodium hydroxide aqueous solution is prepared by mixing sodium hydroxide and deionized water in a mass ratio of 1:13.
[0030] A method for preparing a flame-retardant high-strength composite plastic comprises the following steps: polyethylene terephthalate, modified magnesium oxide, glass fiber and a compatibilizer are mixed according to weight proportions, melt-extruded at a temperature of 190 DEG C, and granulated to obtain the composite plastic.
[0031] Example 2
[0032] A flame-retardant high-strength composite plastic comprises the following components by weight: 105 parts of polyethylene terephthalate, 18 parts of modified magnesium oxide, 3.5 parts of glass fiber and 7 parts of a compatibilizer; the compatibilizer is a styrene-glycidyl methacrylate copolymer.
[0033] Wherein, the preparation method of the modified magnesium oxide comprises the following steps:
[0034] 1) After magnesium oxide and anhydrous ethanol are stirred and mixed, modified cinnamic acid is added for ultrasonic treatment, cysteine and a photoinitiator are added and mixed, and then ultraviolet irradiation is performed, and solids are filtered, washed, and vacuum dried to constant weight to obtain prefabricated magnesium oxide;
[0035] 2) After the prefabricated magnesium oxide and anhydrous ethanol are mixed and preheated, protocatechuic aldehyde is added and stirred at a constant temperature, the mixture is allowed to stand, the solid is filtered out, washed, and vacuum dried to a constant weight to obtain modified magnesium oxide.
[0036] In step 1), the stirring and mixing is stirring at a speed of 350 r / min for 25 minutes; the ultrasonic treatment is ultrasonication at a power of 350 W for 18 minutes; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 7 hours; the washing is washing three times with anhydrous ethanol; the temperature of the vacuum drying is 75°C; the mass ratio of the magnesium oxide, anhydrous ethanol, modified cinnamic acid, cysteine and photoinitiator is 16:48:4.2:2.2:0.11; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0037] In step 2), the constant temperature stirring is stirring at 62° C. for 7 hours; the standing time is 2.5 hours; the washing is washing with anhydrous ethanol three times; the mass ratio of the prefabricated magnesium oxide, anhydrous ethanol and protocatechuic aldehyde is 19.5:65:3.7.
[0038] The preparation method of the modified cinnamic acid comprises the following steps: mixing p-hydroxycinnamic acid and a sodium hydroxide aqueous solution, adjusting the pH value, adding chloroacetic acid, heating and stirring, filtering out solids, washing, and vacuum drying to constant weight to obtain modified cinnamic acid;
[0039] In the preparation of the modified cinnamic acid, the pH value is adjusted to 12; the heating and stirring is stirred at a temperature of 90°C for 7.5 hours; the washing is washed twice with acetone and deionized water alternately; the temperature of the vacuum drying is 80°C; the mass ratio of the p-hydroxycinnamic acid, the sodium hydroxide aqueous solution and the chloroacetic acid is 0.9:11:1; the sodium hydroxide aqueous solution is prepared by mixing sodium hydroxide and deionized water in a mass ratio of 1:13.
[0040] A method for preparing a flame-retardant high-strength composite plastic comprises the following steps: polyethylene terephthalate, modified magnesium oxide, glass fiber and a compatibilizer are mixed according to weight proportions, melt-extruded at 200°C, and granulated to obtain the composite plastic.
[0041] Example 3
[0042] A flame-retardant high-strength composite plastic comprises the following components by weight: 110 parts of polyethylene terephthalate, 20 parts of modified magnesium oxide, 4 parts of glass fiber and 8 parts of a compatibilizer; the compatibilizer is a styrene-glycidyl methacrylate copolymer.
[0043] Wherein, the preparation method of the modified magnesium oxide comprises the following steps:
[0044] 1) After magnesium oxide and anhydrous ethanol are stirred and mixed, modified cinnamic acid is added for ultrasonic treatment, cysteine and a photoinitiator are added and mixed, and then ultraviolet irradiation is performed, and solids are filtered, washed, and vacuum dried to constant weight to obtain prefabricated magnesium oxide;
[0045] 2) After the prefabricated magnesium oxide and anhydrous ethanol are mixed and preheated, protocatechuic aldehyde is added and stirred at a constant temperature, the mixture is allowed to stand, the solid is filtered out, washed, and vacuum dried to a constant weight to obtain modified magnesium oxide.
[0046] In step 1), the stirring and mixing is stirring at a speed of 400 r / min for 30 minutes; the ultrasonic treatment is ultrasonication at a power of 400 W for 20 minutes; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 8 hours; the washing is washing three times with anhydrous ethanol; the temperature of the vacuum drying is 80°C; the mass ratio of the magnesium oxide, anhydrous ethanol, modified cinnamic acid, cysteine and photoinitiator is 16:50:4.5:2.3:0.12; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0047] In step 2), the constant temperature stirring is stirring at 65° C. for 8 hours; the standing time is 3 hours; the washing is washing with anhydrous ethanol three times; the mass ratio of the prefabricated magnesium oxide, anhydrous ethanol and protocatechuic aldehyde is 20:70:4.0.
[0048] The preparation method of the modified cinnamic acid comprises the following steps: mixing p-hydroxycinnamic acid and a sodium hydroxide aqueous solution, adjusting the pH value, adding chloroacetic acid, heating and stirring, filtering out solids, washing, and vacuum drying to constant weight to obtain modified cinnamic acid;
[0049] In the preparation of the modified cinnamic acid, the pH value is adjusted to 13; the heating and stirring is stirring at a temperature of 90°C for 8 hours; the washing is washing with acetone and deionized water alternately twice; the vacuum drying temperature is 80°C; the mass ratio of p-hydroxycinnamic acid, sodium hydroxide aqueous solution and chloroacetic acid is 1.0:12:1.2; the sodium hydroxide aqueous solution is prepared by mixing sodium hydroxide and deionized water in a mass ratio of 1:13.
[0050] A method for preparing a flame-retardant high-strength composite plastic comprises the following steps: polyethylene terephthalate, modified magnesium oxide, glass fiber and a compatibilizer are mixed according to weight proportions, melt-extruded at a temperature of 210 DEG C, and granulated to obtain the composite plastic.
[0051] Comparative Example 1
[0052] Compared with Example 3, the difference in Comparative Example 1 is that p-hydroxycinnamic acid replaces modified cinnamic acid, and the other components, preparation steps and parameters are the same.
[0053] Comparative Example 2
[0054] Compared with Example 3, Comparative Example 2 is different in that modified cinnamic acid is not used, and the other components, preparation steps and parameters are the same.
[0055] Comparative Example 3
[0056] Compared with Example 3, Comparative Example 3 is different in that cysteine is not used, and the other components, preparation steps and parameters are the same.
[0057] Comparative Example 4
[0058] Compared with Example 3, Comparative Example 4 is different in that protocatechuic aldehyde is not used, and the other components, preparation steps and parameters are the same.
[0059] Comparative Example 5
[0060] Compared with Example 3, Comparative Example 5 is different in that no compatibilizer is used, and the other components, preparation steps and parameters are the same.
[0061] The plastic samples prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to the following performance tests, respectively, and the test results are shown in Table 1.
[0062] Tensile strength test: according to GB / T1040-2006;
[0063] Limiting oxygen index test: according to GB / T 2406.2-2009;
[0064] Table 1
[0065]
[0066] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the plastics prepared in Examples 1-3 of the present invention have excellent mechanical strength and flame retardant properties.
[0067] The present invention adopts the modification of hydroxycinnamic acid and successfully introduces an additional carboxyl group. By compounding the modified cinnamic acid with magnesium oxide, not only the active reaction sites are increased, but also the interaction between the carboxyl group and the hydroxyl group is utilized to promote the grafting of cysteine. Furthermore, a Schiff base structure with high thermal stability is introduced through the chemical bond connection between the amino group and the aldehyde group, so that the modified magnesium oxide contains a variety of active functional groups. The introduced organic Schiff base structure is rich in hydrogen bonds, electrostatic effects and coordination bonds, which greatly improves the compactness of the structure, thereby significantly enhancing the mechanical strength and flame retardant properties of the plastic.
[0068] In addition, by modifying magnesium oxide with organic matter and introducing a large number of highly stable benzene ring structures, the compatibility of magnesium oxide in the polyethylene terephthalate system is improved, and the compactness of organic materials is enhanced. By adding a compatibilizer, the dispersibility and interfacial bonding strength of modified magnesium oxide and glass fiber in the system are further enhanced, further improving the mechanical strength and flame retardant properties of the plastic.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A flame retardant high-strength composite plastic, characterized in that: The composition comprises the following components by weight: 100-110 parts of polyethylene terephthalate, 15-20 parts of modified magnesium oxide, 3-4 parts of glass fiber and 6-8 parts of compatibilizer; Wherein, the preparation method of the modified magnesium oxide comprises the following steps: 1) After magnesium oxide and anhydrous ethanol are stirred and mixed, modified cinnamic acid is added for ultrasonic treatment, cysteine and a photoinitiator are added and mixed, and then ultraviolet irradiation is performed, and solids are filtered, washed, and vacuum dried to constant weight to obtain prefabricated magnesium oxide; 2) After prefabricated magnesium oxide and anhydrous ethanol are mixed and preheated, protocatechuic aldehyde is added and stirred at a constant temperature, the mixture is allowed to stand, the solid is filtered out, washed, and vacuum dried to a constant weight to obtain modified magnesium oxide; The preparation method of modified cinnamic acid comprises the following steps: mixing p-hydroxycinnamic acid and sodium hydroxide aqueous solution, adjusting the pH value, adding chloroacetic acid, heating and stirring, filtering solids, washing, and vacuum drying to constant weight to obtain modified cinnamic acid.
2. The flame retardant high-strength composite plastic according to claim 1, characterized in that: In step 1), the stirring and mixing is stirring at a speed of 300-400 r / min for 20-30 min; the ultrasonic treatment is ultrasonic treatment at a power of 300-400 W for 15-20 min; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 6-8 h; the washing is washing three times with anhydrous ethanol; and the temperature of the vacuum drying is 70-80°C.
3. The flame retardant high-strength composite plastic according to claim 1, characterized in that: In step 1), the mass ratio of the magnesium oxide, anhydrous ethanol, modified cinnamic acid, cysteine and photoinitiator is 16:45-50:4-4.5:2.0-2.3:0.10-0.12; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
4. The flame retardant high-strength composite plastic according to claim 1, characterized in that: In step 2), the constant temperature stirring is stirring at 60-65° C. for 6-8 hours; the standing time is 2-3 hours; and the washing is washing with anhydrous ethanol three times.
5. The flame retardant high-strength composite plastic according to claim 1, characterized in that: In step 2), the mass ratio of the prefabricated magnesium oxide, anhydrous ethanol and protocatechuic aldehyde is 19-20:60-70:3.4-4.
0.
6. The flame retardant high-strength composite plastic according to claim 1, characterized in that: In the preparation of the modified cinnamic acid, the pH value is adjusted to 10-13; the heating and stirring is stirring at 90° C. for 7-8 hours; the washing is washing with acetone and deionized water alternately twice; and the vacuum drying temperature is 80° C.
7. The flame-retardant high-strength composite plastic according to claim 1, characterized in that: In the preparation of the modified cinnamic acid, the mass ratio of the p-hydroxycinnamic acid, the sodium hydroxide aqueous solution and the chloroacetic acid is 0.8-1.0:10-12:0.9-1.2; the sodium hydroxide aqueous solution is prepared by mixing sodium hydroxide and deionized water in a mass ratio of 1:
13.
8. The flame-retardant high-strength composite plastic according to claim 1, characterized in that: The compatibilizer is styrene-glycidyl methacrylate copolymer.
9. A method for preparing a flame retardant high-strength composite plastic according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: polyethylene terephthalate, modified magnesium oxide, glass fiber and a compatibilizer are mixed according to weight proportions, melt-extruded at a temperature of 190-210° C., and granulated to obtain the product.
Citation Information
Patent Citations
Synthetic method of cross-linked bagasse xylan-4-acetylaminocinnamate-g-AM
CN109400767A
Sunscreen laminated glass for car window and preparation method of sunscreen laminated glass
CN118046639A